2017
DOI: 10.1101/147702
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

De-novoassembly of zucchini genome reveals a whole genome duplication associated with the origin of theCucurbitagenus

Abstract: The Cucurbita genus (squashes, pumpkins, gourds) includes important domesticated species such as C. pepo, C. maxima and C. moschata . In this study, we present a high-quality draft of the zucchini ( C. pepo ) genome. The assembly has a size of 263 Mb, a scaffold N50 of 1.8 Mb, 34,240 gene models, includes 92% of the conserved BUSCO core gene set, and it is estimated to cover 93.0% of the genome. The genome is organized in 20 pseudomolecules, that represent 81.4% of the assembly, and it is integrated with a gen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 77 publications
2
40
0
Order By: Relevance
“…We identified 195 paralogous syntenic blocks (7773 homoeologous gene pairs) in C. maxima and 170 blocks (7742 gene pairs) in C. moschata, with synonymous substitution rate (Ks) values peaking at 0.32 ( Figure 2A and Supplemental Figures 5 and 6), collectively covering 92.5% and 94.1% of the gene space, respectively. These homoeologous pairs clearly indicated that both C. maxima and C. moschata genomes underwent a wholegenome duplication (WGD) event that was also reported in another Cucurbita species, C. pepo (Montero-Pau et al, 2017), but not observed in other sequenced cucurbits, including cucumber (Huang et al, 2009), melon (Garcia-Mas et al, 2012), watermelon (Guo et al, 2013), and bitter gourd (Momordica charantia) (Urasaki et al, 2017) (Figure 2A).…”
Section: Repeat Sequence Prediction and Gene Annotationsupporting
confidence: 58%
“…We identified 195 paralogous syntenic blocks (7773 homoeologous gene pairs) in C. maxima and 170 blocks (7742 gene pairs) in C. moschata, with synonymous substitution rate (Ks) values peaking at 0.32 ( Figure 2A and Supplemental Figures 5 and 6), collectively covering 92.5% and 94.1% of the gene space, respectively. These homoeologous pairs clearly indicated that both C. maxima and C. moschata genomes underwent a wholegenome duplication (WGD) event that was also reported in another Cucurbita species, C. pepo (Montero-Pau et al, 2017), but not observed in other sequenced cucurbits, including cucumber (Huang et al, 2009), melon (Garcia-Mas et al, 2012), watermelon (Guo et al, 2013), and bitter gourd (Momordica charantia) (Urasaki et al, 2017) (Figure 2A).…”
Section: Repeat Sequence Prediction and Gene Annotationsupporting
confidence: 58%
“…Compared to hundreds of shared markers in previous studies [21], much more cross-species transferable SSR markers in Cucurbita genus were used for chromosome synteny analysis in our study. It might be the case that there had a WGD event leading to the high abundance of SSR markers [8,9], but it's not observed in other sequenced Cucurbitaceae species, such as cucumber [15], melon [48], watermelon [16].…”
Section: The Chromosome Synteny Analysis Between C Pepo and Other Cumentioning
confidence: 99%
“…In 2012, the planting area of pumpkin in China was about 3.8×10 4 Hm 2 , and the total output reached 7.0×10 6 tons (http://faostat3.fao.org/). Cucurbita species have a relatively smaller genome sizes and a greater chromosome numbers compared with other Cucurbitaceous crops [7], and the assembled genome sizes are 271.4 Mb for C. maxima, 269.9 Mb for C. moschata, and 263 Mb for C. pepo, respectively [8,9]. With a long history of cultivation and domestication, the morphological variation of Cucurbita species shows a higher diversity in fruit shape, size and color than other Cucurbitaceae species [10].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic resources and genetic transformation protocols have recently become available in Cucurbita (Montero‐Pau et al, , ; Nanasato, Okuzaki, & Tabei, ; Sun et al, ). Alongside improvements in the characterization of genetic diversity within the crop wild relatives, these resources are facilitating breeding and genetic research (e.g., Holdsworth, LaPlant, Bell, Jahn, & Mazourek, ).…”
Section: Introductionmentioning
confidence: 99%